Nepal Development Update, October 2013 - Kruse, Aurélien; Bajracharya, Roshan Darshan; Mahato, Deb Narayan (World Bank, Kathmandu, 2014)
Nepal's political developments continue to overshadow and impede its economic development. Over the short term, whether the scheduled elections are held and, if so, whether they achieve a modicum of consensus will be a major test. Political instability clouded the outlook in FY2013 and remains the principal source of vulnerability going forward. While Nepal's macroeconomic fundamentals remain stable, sources of vulnerability have not disappeared. Although the financial sector has rebuilt strength, it remains an important source of weakness. Important initiatives to improve the governance environment have been taken, but these initiatives can be amplified further. For FY2014, the baseline scenario is a gradual return to trend, with higher growth and sustainable fiscal expansion. While important psychologically and for some sectors of the economy, the recent depreciation of the Nepal rupee is not expected to hold back growth or to threaten macroeconomic stability. While a revision of the peg with India may eventually be warranted, the report agrees with Nepali policy makers that this is not the time when markets are unstable to move impulsively. Instead, such a major policy shift should be based on clear policy objectives and in-depth analysis of likely economic outcomes, including the long-term impact on Nepal's trade competitiveness. The report is structured as follows: chapter one gives summary; chapter two gives recent economic developments; chapter three gives policies and short- to medium-term development challenges; chapter four presents short and medium-term economic projections; chapter five focuses on bank support and activities; and chapter six presents special focus.